2005
DOI: 10.1124/dmd.104.000836
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 3a-Mediated Metabolism of Buspirone in Human Liver Microsomes

Abstract: ABSTRACT:This study was carried out to determine the metabolic pathways of buspirone and cytochrome P450 (P450) isoform ( Buspirone is the first marketed anxiolytic drug from the azapirone class of compounds (Fulton and Brogden, 1997). It is as effective as the benzodiazepines for the treatment of anxiety, but buspirone produces fewer adverse side-effects such as sedation, motor impairment, and dependence liability (O'Hanlon, 1991). Unlike benzodiazepine anxiolytics, buspirone has little affinity for the ␥-ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
41
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 25 publications
11
41
2
Order By: Relevance
“…). The metabolism of buspirone has been suggested to be mainly mediated by CYP3A and a similar metabolite pattern in HLM was reported in comparison with that in vivo (Jajoo et al, 1989;Zhu et al, 2005). Previously reported metabolite formation data resulted in marginally higher CLu int values (correction for fu inc applied) compared with our substrate depletion data (460 versus 268 l ⅐ min Ϫ1 ⅐ mg Ϫ1 ) (Zhu et al, 2005;Gertz et al, 2010).…”
Section: Gertz Et Alcontrasting
confidence: 48%
“…). The metabolism of buspirone has been suggested to be mainly mediated by CYP3A and a similar metabolite pattern in HLM was reported in comparison with that in vivo (Jajoo et al, 1989;Zhu et al, 2005). Previously reported metabolite formation data resulted in marginally higher CLu int values (correction for fu inc applied) compared with our substrate depletion data (460 versus 268 l ⅐ min Ϫ1 ⅐ mg Ϫ1 ) (Zhu et al, 2005;Gertz et al, 2010).…”
Section: Gertz Et Alcontrasting
confidence: 48%
“…In this study, it has been found that the typical PPT ginsenoside turnover rate in CYP3A4 was much higher (ranging from 12-to 48-fold) than that in CYP3A5, suggesting that CYP3A4 should be the predominant isoform and that CYP3A5 contributed very little to the oxygenation metabolism of ginsenosides. Such a phenomenon has been also widely found for many other typical CYP3A substrates such as buspirone (Zhu et al, 2005) and cyclosporin A.…”
Section: Discussionmentioning
confidence: 95%
“…The fragment ion was shown at m/z 218, suggesting that M6 had a hydroxy group that could be dehydrated. It is known that breaking of the C-N bond between an alkyl group and piperazine ring can occur (Zhu et al, 2005). Our findings suggested that M6 might be a cyclic form arising via cyclization of the aldehyde form (Thompson et al, 1996(Thompson et al, , 2000Singh et al, 2003).…”
Section: Screening Of Microsomes Expressing 13 Isoforms Of Human P450mentioning
confidence: 84%